Characterization of Cr/SiO2/Al2O3 catalyst from Rice Husk using Impregnation Method - Prahadu Susmanto; Yandriani Gusman; M Fajar Ridwan; Endra Hakim Tanara (Universitas Islam Indonesia, 2020)
Rice husk is one of biomass which has very high silica content (18-22%). It can be used as one of support material in the form of SiO2 / Al2O3 which if it is varied with metals, it will produce a catalyst. In this research, a Cr / SiO2 / Al2O3 catalyst was made by using wetness impregnation and dry impregnation methods to obtain the best amount of Cr metal. According to FTIR test results on SiO2 / Al2O3 material, it formed Si-OH bond (3250.2 cm-1), Al-OH (1620 cm-1), Si-O-Si (1410.6 cm-1), O-Al -O (767.8 cm-1). The results of SEM-EDX and Brunauer Emmet Teller (BET) test on variations in the concentration of 0.5 M precursor solution; 1 M; 1.5 M showed that A3 variant had the highest Cr content of 19.79% with a surface area of 68.939 m2 / gr, a pore volume of 0.06675 cc / gr and a pore radius of 19.36 Å. Based on isothermal desorption adsorption curve with nitrogen gas the A3 catalyst variant was classified into type IV with mesoporous structure based on International Union of Pure and Applied Chemistry (IUPAC).